The Effect of Low-Level Laser Therapy on the Viability of Human Dental Pulp Stem Cells: Effect of LLL on the viability of DPSCs - Asnaashari, Mohamad; Shojaeian, Shiva; Mesgharani, Ali; Mehrabinia, Pegah (Journal of Lasers in Medical Sciences, 2022)
Objectives: This study assessed the effect of low-level laser (LLL) irradiation on the viability of dental pulp stem cells (DPSCs). Materials and Methods: In this in vitro experimental study, human DPSCs were purchased from the cell bank of Iranian Genetic Resources and cultured in flasks containing Dulbecco’s modified Eagle’s medium supplemented with 20% fetal bovine serum (FBS) at 37°C, 5% CO2, and 95% humidity. The cells were stored in semi-confluent form, and the culture medium was refreshed every two days. The cells in the control group were not laser-irradiated. The cells in the experimental groups were irradiated with 660 and 808 nm diode lasers with 4.1 J/cm2 energy density. Cell viability was assessed at baseline and after 24, 48, and 72 hours using the methyl thiazolyl tetrazolium (MTT) assay. The effects of laser irradiation, laser wavelength, and time on the percentage of cell viability were analyzed by two-way ANOVA and Tukey’s test. Results: The effects of laser irradiation and its wavelength (P=0.04), time of assessment (P<0.001), and the interaction effect of group and time (P=0.02) on cell viability were significant. Cell viability in 660 and 808 nm laser groups at 48 and 72 hours was higher than that of the control group; however, statistically, only the difference in cell viability between the 660 nm laser and control group at 72 hours was significant (P=0.03). Conclusion: Considering the optimal effect of diode laser irradiation (particularly 660 nm) on the viability of DPSCs, it may be suitable for relevant clinical applications.